2015
DOI: 10.1016/j.sedgeo.2014.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Effective grain size distribution analysis for interpretation of tidal–deltaic facies: West Bengal Sundarbans

Abstract: This is an open access article published under a Creative Commons Attribution-NonCommercial-NoDerivs License (https://creativecommons.org/licenses/by-nc-nd/4.0/), which permits distribution and reproduction for non-commercial purposes, provided the author and source are cited. General rightsCopyright for the publications made accessible via the Queen's University Belfast Research Portal is retained by the author(s) and / or other copyright owners and it is a condition of accessing these publications that users… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 47 publications
2
21
0
Order By: Relevance
“…Interestingly, the deposition rates determined by this and other recent studies (e.g., Rogers et al, 2013;Auerbach et al, 2015;Bomer et al, in review) are similar to the local deposition rates observed across the entire Holocene (0.7-1.0 cm/year; Ayers et al, 2016). Further to the west, where sedimentation has been reduced as a result of the eastward migration of the Ganges River over the past 4000 years, the longterm deposition rates are closer to 0.1-0.2 cm/year (Flood et al, 2015). It would be an oversimplification to imply that this spatial variability stems exclusively from a moving sediment supply.…”
Section: Spatio-temporal Variability and Future Implicationssupporting
confidence: 89%
See 1 more Smart Citation
“…Interestingly, the deposition rates determined by this and other recent studies (e.g., Rogers et al, 2013;Auerbach et al, 2015;Bomer et al, in review) are similar to the local deposition rates observed across the entire Holocene (0.7-1.0 cm/year; Ayers et al, 2016). Further to the west, where sedimentation has been reduced as a result of the eastward migration of the Ganges River over the past 4000 years, the longterm deposition rates are closer to 0.1-0.2 cm/year (Flood et al, 2015). It would be an oversimplification to imply that this spatial variability stems exclusively from a moving sediment supply.…”
Section: Spatio-temporal Variability and Future Implicationssupporting
confidence: 89%
“…This study will focus on a portion of the Sundarbans National Forest (SNF), a relatively pristine mangrove forest located in southwestern Bangladesh (Figure 1). The total extent of the Sundarbans reaches across political boundaries into India, expressing a continuum of fluvial and tidal forces with increased distance from the modern Ganges-Brahmaputra-Meghna River mouth (Allison and Kepple, 2001;Rogers et al, 2013;Flood et al, 2015Flood et al, , 2018. Immediately to the north of the SNF is an inhabited region where the construction of earthen embankments ("polders") has resulted in a substantial modification of the tidal prism, leading to tidal amplification and extensive network reorganization (e.g., Pethick and Orford, 2013;Wilson et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The overarching trend would suggest a strong relationship between zirconium and 692 coarse grained sediment, as these sites are considered to reflect upward fining sequences 693 (e.g., Allison et al, 2003;Flood et al, 2015). In particular the trend consists of 694 coarse/very coarse-silt and sand with a concomitant relationship between coarse clay and 695 medium/coarse-silt for rubidium.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Particlesize determinations are common practice in powder technology, which includes several chemical and industrial activities (Burgess et al, 2004;Allen, 2013). However, such measurements are not limited to industrial purposes alone as they have various applications in the earth sciences (e.g., Sahu, 1964;Weltje and von Eynatten, 2004;Flood et al, 2015).…”
Section: Introductionmentioning
confidence: 99%